MICA and KIR: Immunogenetic Factors Influencing Left Ventricular Systolic Dysfunction and Digestive Clinical Form of Chronic Chagas Disease - Ayo, Christiane Maria; Bestetti, Reinaldo Bulgarelli; de Campos Junior, Eumildo; Ronchi, Luiz Sérgio; Borim, Aldenis Albaneze; Brandão, Cinara Cássia; de Matttos, Luiz Carlos (Frontiers in Immunology, 2021)
Tissue damage observed in the clinical forms of chronic symptomatic Chagas disease seems to have a close relationship with the intensity of the inflammatory process. The objective of this study was to investigate whether the MICA (MHC class I-related chain A) and KIR (killer cell immunoglobulin-like receptors) polymorphisms are associated with the cardiac and digestive clinical forms of chronic Chagas disease. Possible influence of these genes polymorphisms on the left ventricular systolic dysfunction (LVSD) in patients with chronic Chagas heart disease was also evaluated. This study enrolled 185 patients with positive serology for Trypanosoma cruzi classified according to the clinical form of the disease: cardiac (n=107) and digestive (n=78). Subsequently, patients with the cardiac form of the disease were sub-classified as with LVSD (n=52) and without LVSD (n=55). A control group was formed of 110 healthy individuals. Genotyping was performed by polymerase chain reaction-sequence specific oligonucleotide probes (PCR-SSOP). Statistical analyzes were carried out using the Chi-square test and odds ratio with 95% confidence interval was also calculated to evaluate the risk association. MICA-129 allele with high affinity for the NKG2D receptor was associated to the LVSD in patients with CCHD. The haplotype MICA*008~HLA-C*06 and the KIR2DS2-/KIR2DL2-/KIR2DL3+/C1+ combination were associated to the digestive clinical form of the disease. Our data showed that the MICA and KIR polymorphisms may exert a role in the LVSD of cardiac patients, and in digestive form of Chagas disease.